Sostenibiligrafía de la Universidad (Papeles, 2009)
The following document presents a discussion about the role of the university in the future concerning the formation of sustainable professional-citizens, and their commitment with the planet and human life sustainability. It questions the technical, economical and scientific model of sustainability guided by the lineal and evolution progress idea, promoting a consumer society and moving away from a real human possibility and its entailed aims such as the nature and the development of social awareness; at the same time, this model has strongly influenced the epistemological assumptions of the higher education, which are evidenced in the constant fragmentation of knowledge, and has disqualified the university to react to the social problems of our days.
Keywords: higher education, sustainable social development, professional-citizens, fragmented knowledge paradigm, complexity paradigm.